The Student of Error Analysis and Remedial Program in Working on the Story of Comparative Material and Turning Value - Melania Eva Wulanningtyas; Suswanti .; Nafida Hetty Marhaeni (Daya Matematis: Jurnal Inovasi Pendidikan Matematika, 2020)
Problem solving mathematics error in a matter of story on ratio material worth and turn around values still often occur, so we need a remedial program to minimize these errors. For this reason, this study aims to determine the types of errors, remedial program steps and types of errors after the remedial program. This research is a qualitative descriptive study with the data collection method uses tests, interviews, and personal documents. The study was conducted at eighth grade of SMP Pangudi Luhur 1 Yogyakarta. This study applies a layered validation strategy in the form of triangulation techniques, Focus Group Discussion (FGD) and the involvement of resource persons and experts. The results showed that the dominant error in the form of an error did not understand the command problem with a percentage of 43%, the error shown if every step taken by students was correct but the final result given was not a solution done with a percentage of 80% and a calculation error with a percentage of 20%. After the results are obtained remediation efforts are made. Based on the remediation results that have been made, there is a decrease in 2 categories of dominant student errors, namely mistakes not understanding the question command to a percentage of 31%, errors that are shown if each step taken by students is correct but the end result given is not a completion done to 60%. Thus, the remediation program makes fewer types of mistakes made by students than before remediation.